Narrative setting and dramatic poetry - Kuntz, Mary. (Mnemosyne, Supplements, 1993)
This volume evaluates a single element of tragic art, namely the way in which narrative descriptions of place participate in the poetry of tragedy. They join together structures of the theater to create a context for tragic performance, and ultimately reflect upon tragedy's connection to earlier narrative forms and to the traditional tales that regularly supply tragic plots. The first part of this book examines the introductory function of spatial descriptions and the peculiar resources offered to the playwright by cult settings. In the second part, the spatial oppositions, that are inherent structuring devices in traditional tales, are taken up in chapters treating the motif of exile in extant tragedy.